Pengaruh Citra Perusahaan Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada PT. Mayora Melalui Platform E-Commerce Tokopedia Dan Shopee - Vandina Larasati; Achsanul Nashir (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This Research aimed to analyze “The Influence of Corporate image and service Quality on Customer Loyalty at PT Mayora Through the Tokopedia and Shopee E-Commerce Platforms.” Amidst intense competition inthe fast Moving Consumer Goods (FMCG) industry, a positive corporate image and satisfactory servicequality were crucial factors in maintaining customer loyalty. This research used a quantitative approach totest the hypothesis regarding the relationship between corporate image, service quality, and customerloyalty. Data was collected through questionnaires distributed to PT Mayora Customers who shoppedthrough e-commerce platforms and analyzed using multiple linear regression. The result of this researchwere expected to provide empirical insights for PT Mayora and other companies in the FMCG industry informulating strategies to increase customer loyalty through effective corporate image management and service quality. Keywords: Corporate Image, Service Quality, Customer Loyality, FMCG, E-Commerce